Pemberdayaan Ibu Persatuan Istri Tentara (Persit) Dalam Penanaman Dan Pemanfaatan Tanaman Obat Keluarga (Toga - putu indah budiapsari; Ni Wayan Winianti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Family medicinal plants have various benefits besides being easy to obtain as well as reducing the economic burden on the family in buying conventional medicines. The army wife union (Persit) is a group of women whose members are the wives of active soldiers. The dormitory where the soldiers lived there were a lot of medicinal plants that had not been fully utilized to treat various diseases. The purpose of this service activity is to empower Persit members to properly and properly utilize and cultivate toga. The results of this service, most of Persit members already know the types of family medicinal plants, but there are some people who do not know how to use and process them. The medicinal plants that are often used are cucumber, betel leaf, ginger, guava, cinnamon, turmeric, sembung, and aloe vera.